The Effectiveness of Direct Trade between China and Near-Border Subjects of the Russian Federation - Zharikov, Mikhail Vyasheslavovich (Economy of Regions, 2016)
The subject matter of this article is the mutual international settlements between Russia (i.e. its border regions) and China in yuans. An advantage of such settlements is determined by the amount of money which can be spared by the Russian importers of Chinese products in case of direct trade. The topic of the article encompasses the analysis of export-import operations and national currencies’use, in particular, the yuan, in the cross-border settlements between Russia and China. The objective of this article is to reveal the role of China in the international activities of the Russian near-border regions on the basis of the analysis of export and import statistics database. The hypothesis of this article is that the dynamics of Chinese imports to the Russian nearborder regions correlates with the amount of the yuans traded on the Moscow Stock Exchange. The article produces forecasts of Chinese imports to the Russian near-border regions and the amount of money, which can be spared by the Russian importers in the case of a transition in bilateral settlements to the yuan. The outcomes of the article include the calculated indicators of the efficiency of the direct trade between China and Russia and of the coverage of Chinese imports in the Russian near-border regions by the yuan. The findings of this article are recommended to Russian inporters as a reference point to increase the profitability of export-import operations with China, and to federal and local governments to create the Russian external economic strategy. The authors comes to the conclusion that if the Chinese imports to the Russian border region were in the yuan, then the yuans volume of trade on the Russian foreign exchange market would allow the direct settlements with China.